Empirical essays in institutional and organizational economics - Esther Chevrot-Bianco (University of Copenhagen, Department of Economics, 2021)
This Ph.D. dissertation consists of three chapters that constitute independent research articles. Each chapter of the thesis focuses on the interplay between economic outcomes and different social phenomena, namely social networks (chapter 1) and social preferences (chapters 2 and 3). The first chapter highlights the role of social networks for board opportunities in the corporate sector. I find that the main beneficiaries of a board gender quota implemented in Denmark are women with existing family and spousal networks connected to firms' boards. The second chapter examines the role of social preferences in leadership. It shows that CEOs whose leadership style is grounded in strong personal values are more stakeholder-oriented and have a positive effect on firm performance. The third chapter contributes to the debate on the relationship between market participation and moral universalism: the extent to which people exhibit the same level of morality towards strangers and ingroup members. Using a field experiment in Greenland, it adds evidence that market participation correlates positively with moral universalism.
Keywords: 330